Review of Andrew F. Jones, “Circuit Listening: Chinese Popular Music in the Global 1960s” (2020) (Sound Stage Screen, 2021)
Andrew F. Jones. Circuit Listening: Chinese Popular Music in the Global 1960s. Minneapolis: University of Minnesota Press, 2020. 304 pp. ISBN 9781517902070.